Plano de Logística Sustentável – a percepção dos servidores sobre o processo de implantação na Universidade Federal do Pampa - Tolfo, Silvana Dalmaso (2017)
The theme of sustainability and sustainable development has been gaining prominence in the last decades, due to the need to take care of the environment, mainly because of the patterns of consumption that reflect in the natural resources used, a greater proportion than the capacity of regeneration or replenishment by natural biological processes occurring on our planet. In the Public Administration, the theme is taking shape through Programs and Projects, among them, the mandatory implementation in the Federal Public Organs, the Sustainable Logistics Management Plan - PLS, which is an instrument that aims to establish guidelines and a set of actions for the insertion of sustainability attributes and rationalization of spending in public institutions. At UNIPAMPA, the PLS was initially developed to comply with the legislation and is currently under review for subsequent effective implementation at the University. Thus, the objective of this study was to ascertain the understanding about sustainability and the Sustainable Logistics Management Plan - PLS, in the perception of the employees of the Federal University of Pampa. For this purpose, a questionnaire was used, which was answered by 365 servers, where it was sought to ascertain the servers' knowledge about sustainability in Public Management and UNIPAMPA's PLS, in order to contribute to the qualification and implementation of PLS in the University Units and in the Rectory. The sample was stratified by Unit so that the results could be generalized to the population surveyed. The data were analyzed through frequency analysis and descriptive statistics, where it was observed that the servers have a low level of knowledge about sustainability in Public Management and on the PLS of the Institution. On the other hand, the actions present in the PLS were evaluated as important or very important, which allows to infer that, when implemented, the Plan will have a good acceptance by the servers. In addition, were collected suggestions about sustainable actions or practices to be implemented at the University or included in the PLS, among which stand out issues related to the awareness and dissemination of the Plan, as well as selective collection, energy and impressions. Finally, contributions were added for the qualification and implementation of the PLS in the University Units and in the Rectory of UNIPAMPA.